(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Employee mental health issues are gaining increasing attention in modern human resource management. The digital transformation of the Society 5.0 era has blurred the boundaries between personal and professional life (Fukuyama, 2020), requiring organizations to balance work demands and personal needs through a Work Life Balance (WLB) approach. This article uses a conceptual approach based on a literature review to develop the WSEM Model, which explains the relationship between WLB and mental health with Perceived Organizational Support (Eisenberger et al., 1986) and Employee Engagement (Schaufeli & Bakker, 2004) as mediators. WLB is viewed as a work resource that protects individuals from excessive pressure and encourages engagement (Bakker & Demerouti, 2007). This article expands the literature by adding the Society 5.0 dimension and provides guidance for organizations in designing flexible work policies and empathy-based psychological support to maintain workforce well-being.